Oral almitrine in treatment of acute respiratory failure and cor pulmonale in patients with an exacerbation of chronic obstructive airways disease. Issue 7 (July 1991) - Bardsley, P A; Tweney, J; Morgan, N; Howard, P
Abstract : The effects of oral almitrine bismesylate, a respiratory stimulant that acts on peripheral arterial chemoreceptors, was studied in patients with chronic obstructive airways disease and hypoxaemic cor pulmonale. Twenty three patients admitted to hospital with an acute exacerbation of ventilatory failure were randomised to receive either almitrine 100 mg twice a day reducing to 50 mg twice a day over 48 hours or placebo in addition to conventional treatment. On admission the mean (SE) values for blood gas tensions were PaO2 4.8 (0.3) and PaCO2 7.7 (0.3) kPa in the 12 patients who received almitrine and PaO2 4.9 (0.1) and PaCO2 7.6 (0.3) kPa in the 11 who received placebo. After three hours of oxygen therapy at 1 1/min there was a similar rise in PaO2 in both groups, 6.4 (0.2) kPa in those receiving almitrine and 6.6 (0.4) kPa in those receiving placebo. After 24 hours of oxygen therapy values of PaO2 were again similar at 6.3 (0.8) kPa and 6.7 (2.2) kPa respectively. Arterial blood gas tensions improved during the study in those who survived but no significant differences were apparent between the two groups. There were six deaths, five in the almitrine group and one in the placebo group. There were no differences between the groups in respiratory rate, results of spirometry, oxygen requirement, or degree of dyspnoea (on visual analogue scale). The results did not show any benefit from oral almitrine in patients with acute respiratory failure secondary to chronic obstructive airways disease. Plasma almitrine concentrations, however, were often below the optimum therapeutic range, suggesting impaired drug absorption.